The Medieval Architecture of Cistercian Nunneries in the Low Countries (Bulletin KNOB, 2004)
In the Low Countries and more particularly in the county of Flanders, the duchy of Brabant and the principality of Liège no less than eighty-five Cistercian nunneries were founded during the Middle Ages. A general history of this movement still needs to be written. The traditional historiography mainly focused on the foundation process of the nunneries, on their patrons and on how the early communities were integrated into the Cistercian order or became beguinages.Apart from the monographs on abbeys and some regional studies, there has also been interest in the spiritual work and life of the Cistercian saints who lived in the Low Countries in the thirteenth century: Beatrice of Nazareth, Ida of Léau, Alice of Schaarbeek, Ida of Louvain, Ida of Nivelles, Julienne of Cornillon, etc.More recent is the interest of scholars in the fifteenth century reform movements that embraced not only the Cistercian nunneries but a large part of the monastic life in the Burgundian Low Countries. A reassertion of the (spiritual) life of women in the Middle Ages, notably by gender-studies, has also aroused interest in nuns and nunneries.Our aim here is to make more concrete the architectural environment of the medieval Cistercian nuns in the Low Countries, by collecting the scarce remains, organising them typologically and trying to define the evolution from the early thirteenth to the mid sixteenth century.